Are we prepared to deliver gene‐targeted therapies for rare diseases?. Issue 1 (24th January 2023) - Yu, Timothy W.; Kingsmore, Stephen F.; Green, Robert C.; MacKenzie, Tippi; Wasserstein, Melissa; Caggana, Michele; Gold, Nina B.; Kennedy, Annie; Kishnani, Priya S.; Might, Matthew; Brooks, Phillip J.; Morris, Jill A.; et al.
Abstract: The cost and time needed to conduct whole‐genome sequencing (WGS) have decreased significantly in the last 20 years. At the same time, the number of conditions with a known molecular basis has steadily increased, as has the number of investigational new drug applications for novel gene‐based therapeutics. The prospect of precision gene‐targeted therapy for all seems in reach… or is it? Here we consider practical and strategic considerations that need to be addressed to establish a foundation for the early, effective, and equitable delivery of these treatments.